Astro Phamacological Perspective of Vitamins - Dimri, Mayank; Rajwar, Virbal Singh; Kush, Luv (Asian Journal of Pharmaceutical Research and Development, 2020)
The pharmacological connectivity of vitamins with astrology is new concept of complementary medicine. Vitamins have chemo - preventive value in therapeutics. The element crisis completes their solubility on the basis of sun and moon traits.